Patient Understanding of the Risks and Benefits of Biologic Therapies in Inflammatory Bowel Disease: Insights from a Large-scale Analysis of Social Media Platforms. Issue 7 (July 2017) - Martinez, Bibiana; Dailey, Francis; Almario, Christopher V.; Keller, Michelle S.; Desai, Mansee; Dupuy, Taylor; Mosadeghi, Sasan; Whitman, Cynthia; Lasch, Karen; Ursos, Lyann; Spiegel, Brennan M.R.
Abstract : Background: Few studies have examined inflammatory bowel disease (IBD) patients' knowledge and understanding of biologic therapies outside traditional surveys. Here, we used social media data to examine IBD patients' understanding of the risks and benefits associated with biologic therapies and how this affects decision-making. Methods: We collected posts from Twitter and e-forum discussions from >3000 social media sites posted between June 27, 2012 and June 27, 2015. Guided by natural language processing, we identified posts with specific IBD keywords that discussed the risks and/or benefits of biologics. We then manually coded the resulting posts and performed qualitative analysis using ATLAS.ti software. A hierarchical coding structure was developed based on the keyword list and relevant themes were identified through manual coding. Results: We examined 1598 IBD-related posts, of which 452 (28.3%) centered on the risks and/or benefits of biologics. There were 5 main themes: negative experiences and concerns with biologics (n = 247; 54.6%), decision-making surrounding biologic use (n = 169; 37.4%), positive experiences with biologics (n = 168; 37.2%), information seeking from peers (n = 125; 27.7%), and cost (n = 38; 8.4%). Posts describing negative experiences primarily commented on side effects from biologics, concerns about potential side effects and increased cancer risk, and pregnancy safety concerns. Posts on decision-making focused on nonbiologic treatment options, hesitation to initiate biologics, and concerns about changing or discontinuing regimens. Conclusions: Social media reveals a wide range of themes governing patients' experience and choice with IBD biologics. The complexity of navigating their risk–benefit profiles suggests merit in creating online tailored decision tools to support IBD patients' decision-making with biologic therapies. Abstract : Article first published online 13 April 2017.Supplemental Digital Content is Available in the Text.